Performance analysis of solar water heater by using TiO2 nanofluids. (2020) - Ram kumar, R.; Jaya Suthahar, S.T.; Sakthivel, C.; Vijayan, V.; Yokeshwaran, R.
Abstract: In the industrial sectors, heat must be transferred either to insert energy into the system or to remove the energy produced in the system. In this research work, the investigations on convection heat transfer and pressure drop characteristics of water and TiO2 nanofluids. TiO2 nanofluid of 0.3% volume concentration is used for experimentation. Copper rod of 3 mm diameter is used to prepare the riser tube of 2 m length. The maximum efficiency attained from the TiO2 nanofluids plane tube collector is 58%.